Potential pitfalls of CRISPR/Cas9‐mediated genome editing - Peng, Rongxue; Lin, Guigao; Li, Jinming (The FEBS journal, 2016)
Recently, a novel technique named the clustered regularly interspaced short palindromic repeat (CRISPR)/CRISPR‐associated protein (Cas)9 system has been rapidly developed. This genome editing tool has improved our ability tremendously with respect to exploring the pathogenesis of diseases and correcting disease mutations, as well as phenotypes. With a short guide RNA, Cas9 can be precisely directed to target sites, and functions as an endonuclease to efficiently produce breaks in DNA double strands. Over the past 30 years, CRISPR has evolved from the ‘curious sequences of unknown biological function’ into a promising genome editing tool. As a result of the incessant development in the CRISPR/Cas9 system, Cas9 co‐expressed with custom guide RNAs has been successfully used in a variety of cells and organisms. This genome editing technology can also be applied to synthetic biology, functional genomic screening, transcriptional modulation and gene therapy. However, although CRISPR/Cas9 has a broad range of action in science, there are several aspects that affect its efficiency and specificity, including Cas9 activity, target site selection and short guide RNA design, delivery methods, off‐target effects and the incidence of homology‐directed repair. In the present review, we highlight the factors that affect the utilization of CRISPR/Cas9, as well as possible strategies for handling any problems. Addressing these issues will allow us to take better advantage of this technique. In addition, we also review the history and rapid development of the CRISPR/Cas system from the time of its initial discovery in 2012. Recently, a novel genome editing technique named CRISPR/Cas9 which can be applied in many fields has been rapidly developed. Albeit widely used, this technique has many potential pitfalls, including Cas9 activity, target sites selection and sgRNAs design, delivery methods, off‐target effects, and the incidence of HDR. Solving these problems helps with the utilization of CRISPR/Cas9 system.